Issues in robust and networked control systems - Lu, Lilei (2008)
This thesis presents research results on control and fltering of discrete-time linear systems. The thesis is divided into two parts, the first is on control and fltering of uncertain linear systems with polytopic uncertainties and the second on control and fltering of networked control systems.